Preparation method of coated metal-graphene composite heat-conducting film

By roughening and patterning the metal film, the graphene film and the metal film form an integrated structure, solving the problem of the adhesive affecting the thermal conductivity and achieving efficient thermal conductivity and stable combination.

CN119697943APending Publication Date: 2025-03-25NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671312.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing thermal conductive film needs to be added to enhance the metal adhesion during the preparation process, but the addition of the adhesive will affect the thermal conductivity.

Method used

By roughening and patterning the metal film, the contact area between the graphene film and the metal film is increased, and the graphene film and the metal film are connected through small holes to form an integrated structure, avoiding the use of adhesives.

Benefits of technology

It achieves the improvement of thermal conductivity without the need for adhesive addition, ensuring the close contact and stable bond between the graphene film and the metal film, and reducing the possibility of graphene film falling off.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119697943A_ABST
    Figure CN119697943A_ABST
Patent Text Reader

Abstract

A preparation method of a coated metal-graphene composite heat conduction film comprises the steps that a metal film is subjected to roughening and patterning treatment, then the metal film is sequentially soaked in a diluted hydrochloric acid solution, deionized water and ethyl alcohol to be subjected to ultrasonic cleaning, an oxide layer and impurities on the metal surface are removed, and the metal film is aired at the room temperature; the metal film is soaked in the graphene oxide solution, the deposition thickness of the coated graphene film is controlled by adjusting the reaction temperature and the reaction time, and after the reaction is finished, the metal film is taken out and dried to obtain the metal film which is preliminarily coated with the reduced graphene oxide, namely the composite film; the composite film is subjected to 950-1100 DEG C high-temperature treatment, so that a defect structure in the graphene film is repaired, and finally, the graphene-metal composite heat-conducting film with excellent heat-conducting property is obtained through calendering. The technical scheme provided by the invention has the advantage that no adhesive needs to be added, so that the heat-conducting property is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of thermally conductive materials, and in particular, relates to a method for preparing a coated metal-graphene composite thermally conductive film. Background Art

[0002] Currently, the thermal conductive products widely used in electronic products are mainly artificial graphite films and graphene thermal conductive films. However, the production process of such products is complex, energy consumption is high, and more importantly, their longitudinal thermal conductivity is not high, only in the single digit. Carbon-metal composite thermal conductive films have become an important field for the development of thermal conductive film products due to their simple production, low cost, and high longitudinal thermal conductivity. However, when preparing carbon-metal composite thermal conductive materials, in order to improve the adhesion to the metal, various adhesives or binders are often added to the carbon slurry. The addition of adhesives or binders will significantly affect the thermal conductivity of the final thermal conductive product. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present application provides a method for preparing a coated metal-graphene composite thermally conductive film which does not require the addition of an adhesive and thus has good thermal conductivity.

[0004] In order to solve the above technical problems, the technical solution adopted in the present application is: a method for preparing a coated metal-graphene composite thermal conductive film, the steps of the method comprising:

[0005] (1) Roughening and patterning of metal film: The metal film is placed between two pieces of sandpaper and a concave-convex structure is formed on the surface of the metal film by rolling. Then, the roughened metal film is patterned by laser cutting to form small holes.

[0006] (2) Cleaning and drying: The metal film obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0007] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution, and subjecting it to high pressure homogenization treatment, stirring and diluting it to a desired concentration to obtain a well-exfoliated graphene oxide solution;

[0008] (4) preparing a composite film by reduction deposition: immersing the metal film in step (2) in the graphene oxide solution of the target concentration obtained in step (3), adjusting the reaction temperature and reaction time to control the deposition thickness of the coated graphene film, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide, i.e., a composite film;

[0009] (5) Preparation of composite thermal conductive film by high temperature reduction: The composite film obtained in step (4) is subjected to high temperature treatment at 950-1100° C. to repair the defective structure in the graphene film, and finally a graphene-metal composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0010] Furthermore, the metal film described in step (1) is selected from one of copper foil, aluminum foil and silver foil.

[0011] Furthermore, the metal film in step (1) is made of copper foil, because copper has better thermal conductivity and copper foil is mostly used for metal composite films in the field of thermal conductivity.

[0012] Furthermore, the thickness of the metal film in step (1) is 20-50 μm.

[0013] Furthermore, the rolling pressure in step (1) is selected to be 10-30 MPa.

[0014] Furthermore, the aperture of the small holes described in step (1) is 0.5-2 mm, and the spacing is 1-5 mm; the shape of the hole is not necessarily circular, and other shapes are acceptable. The purpose of providing the small holes is only to allow the graphene on both sides of the copper foil to be connected to each other, so that the composite film has better integrity and better connection with the copper foil; the surface roughening is to increase the bonding area between the graphene film on each side of the metal film and the metal film, reducing the possibility of falling off, and the hole making can further connect the graphene films on both sides of the metal film through the holes made on the metal film during film formation, further reducing the possibility of graphene film falling off.

[0015] Furthermore, the required concentration described in step (3) is that the concentration of the graphene oxide solution is ≥1wt%. The concentration affects the deposition rate. The higher the concentration, the faster the deposition rate.

[0016] Furthermore, the overall thickness of the composite film obtained in step (4) does not exceed 100um, and the thickness of the composite film (the thickness here is the sum of the thickness of a metal film and the thickness of the graphene films on both sides) and the thickness of the metal film are set in the range of 1:0.25-1.

[0017] Furthermore, the reaction temperature and reaction time in step (4) are 35-45° C. for 5-8 h.

[0018] Furthermore, the composite membrane obtained in step (5) is subjected to a high temperature treatment at 1000°C.

[0019] Advantages and beneficial effects of this application:

[0020] 1. The present application relates to a coated metal-graphene composite thermal conductive film: firstly, the metal film is roughened and patterned to improve the bonding strength between the metal and the graphene film. Surface roughening mainly refers to stamping the surface of the metal film with sandpaper to make the surface present a concave-convex structure. Patterning refers to cutting the metal film to form regularly distributed small holes on its surface that penetrate its thickness. Then, the roughened and patterned metal film is immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning in turn. After drying, it is placed in a graphene oxide (GO) solution of different concentrations. The reduction of graphene oxide by metal is utilized to realize the reduction deposition of graphene oxide on the surface of the metal film. The thickness of the coated graphene film is controlled by controlling the reaction time and the reaction temperature. Then, it is taken out and dried to obtain a metal film initially coated with reduced graphene oxide. The metal film is further subjected to high temperature treatment to repair the defective structure in the graphene film. Finally, it is subjected to pressure treatment to obtain a metal film preliminarily coated with reduced graphene oxide. The invention discloses a graphene-metal composite thermally conductive film having excellent thermal conductivity. The specific process for preparing the thermally conductive film mentioned above in the present application can roughen the surface of the metal film to make the metal surface present a concave-convex structure, thereby increasing the contact area between the graphene film and the underlying metal film, thereby improving the bonding strength between the metal and the graphene film. In addition, by patterning, small holes that penetrate the thickness of the metal film and are regularly distributed are formed on the metal film, so that the graphene films covered on the upper and lower surfaces of the metal film are connected to each other through the distributed small holes to form countless rivet points, thereby forming an integrated structure with the metal film, and making the graphene film more tightly cover the metal layer, thereby further reducing the possibility of the graphene film falling off from the metal film, and no adhesive is needed. Moreover, since the metal and the graphene film are integrated, the metal and the graphene film can be in close contact, so the metal-graphene composite thermally conductive film obtained by the present patent has good thermal conductivity.

[0021] 2. The preparation process of the composite film of the present application does not use an adhesive, so the resulting metal-graphene composite thermally conductive film has good thermal conductivity.

[0022] 3. The method of the present application partially reduces the graphene oxide through reduction deposition, and it still needs to rely on the following high-temperature treatment to be completely reduced, and it still mainly relies on high-temperature treatment. Here, low-temperature reduction is only a means to achieve the combination of graphene film and metal film; the high-temperature treatment of the present application can repair the defect structure in the graphene film. The defect structure refers to the oxygen-containing groups that have not been removed in the graphene oxide on the one hand, and the metal oxide on the surface of the metal film on the other hand; calendering only needs to flatten the composite film to increase the density of the graphene film and enhance the thermal conductivity.

[0023] 4. The metal film of the present application can be made of aluminum foil, silver foil or copper foil, etc., and copper foil is particularly used because copper has better thermal conductivity. In the field of thermal conductivity, copper foil is mostly used for metal composite films. The present application forms a number of through holes by shearing in the thickness direction of the metal film, so that the graphene attached to the opposite sides of the metal film in the thickness direction can be connected to each other, achieving a more stable combination with the metal film, making the composite film more integrated, without the need for adhesives, and effectively improving the thermal conductivity of the final coated metal-graphene composite thermally conductive film. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Process flow chart of the preparation method of the coated metal-graphene composite thermally conductive film of the present application. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments and drawings to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only preferred embodiments, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The preparation process flow chart of the composite membrane of the present application can be specifically referred to in the attached Figure 1 shown.

[0027] Example 1

[0028] (1) Roughening and patterning of copper foil: The copper foil is placed between two sheets of sandpaper (commercially available sandpaper can be used) and a concave-convex structure is formed on its surface by rolling, that is, the concave-convexity on the sandpaper is transferred to the upper and lower surfaces of the copper foil by the pressure of rolling; then the roughened copper foil is patterned by laser cutting to form small holes, which are through holes formed in the thickness direction of the copper foil; the thickness of the copper foil selected above is 20 μm; the rolling pressure is selected to be 10 MPa, and the mesh number of the sandpaper is 100 mesh; the aperture of the small holes is 1 mm, and the spacing between the holes is 3 mm;

[0029] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0030] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0031] (4) Preparation of composite film by reduction deposition: the metal film obtained in step (2) is immersed in the graphene oxide solution of the target concentration obtained in step (3), and then reacted at 40° C. for 8 h. After the reaction is completed, it is taken out and dried to obtain a metal film preliminarily coated with reduced graphene oxide, i.e., a composite film;

[0032] (5) Preparation of composite thermal conductive film by high temperature reduction: The composite film obtained in step (4) is subjected to high temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-metal composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0033] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.25, and the thermal conductivity of the graphene-metal composite thermally conductive film finally obtained is tested to be 564.97 W / mK.

[0034] Example 2

[0035] (1) Copper foil roughening and patterning: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling; the roughened copper foil is patterned by laser cutting to form small holes; the thickness of the copper foil selected is 30 μm, and the surface roughness is controlled by the thickness of the sandpaper and the rolling pressure; the rolling pressure is 10 MPa, and the mesh number of the sandpaper is 100 mesh; the aperture of the small holes is 1 mm, and the spacing is 3 mm;

[0036] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0037] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0038] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 6 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0039] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) is subjected to high-temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-copper composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0040] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.5, and the thermal conductivity of the obtained graphene-copper composite thermally conductive film is tested to be 542.17 W / mK.

[0041] Example 3

[0042] (1) Copper foil roughening and patterning: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling; the roughened copper foil is patterned by laser cutting to form small holes; the thickness of the copper foil selected is 40 μm, and the surface roughness is controlled by the thickness of the sandpaper and the rolling pressure; the rolling pressure is 10 MPa, and the mesh number of the sandpaper is 100 mesh; the aperture of the small holes is 1 mm, and the spacing is 3 mm;

[0043] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0044] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0045] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 5 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0046] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) is subjected to high-temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-copper composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0047] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.75, and the thermal conductivity of the obtained graphene-copper composite thermally conductive film is tested to be 525.42 W / mK.

[0048] Example 4

[0049] (1) Copper foil roughening and patterning: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling; the roughened copper foil is patterned by laser cutting to form small holes; the thickness of the copper foil selected is 40 μm, and the surface roughness is controlled by the thickness of the sandpaper and the rolling pressure; the rolling pressure is 10 MPa, and the mesh number of the sandpaper is 100 mesh; the aperture of the small holes is 1 mm, and the spacing is 3 mm;

[0050] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0051] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0052] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 5 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0053] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) is subjected to high-temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-copper composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0054] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.75, and the thermal conductivity of the obtained graphene-copper composite thermally conductive film is tested to be 516.13 W / mK.

[0055] Example 5

[0056] (1) Roughening and patterning of copper foil: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling; the roughened copper foil is patterned by laser cutting to form small holes; the thickness of the copper foil is 30 μm, and the surface roughness is controlled by the thickness of the sandpaper and the rolling pressure; the rolling pressure is 10 MPa, and the mesh size of the sandpaper is 100 mesh; the aperture of the small holes is 0.5 mm, and the spacing is 2 mm;

[0057] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0058] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0059] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 6 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0060] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) is subjected to high-temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-copper composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0061] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.5, and the thermal conductivity of the obtained graphene-copper composite thermally conductive film is tested to be 518.73 W / mK.

[0062] Example 6

[0063] (1) Roughening and patterning of copper foil: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling; the roughened copper foil is patterned by laser cutting to form small holes; the thickness of the copper foil is 30 μm, and the surface roughness is controlled by the thickness of the sandpaper and the rolling pressure; the rolling pressure is 10 MPa, and the mesh number of the sandpaper is 100 mesh; the aperture of the small holes is 1.5 mm, and the spacing is 4 mm;

[0064] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0065] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0066] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 5 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0067] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) is subjected to high-temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-copper composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0068] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.5, and the thermal conductivity of the obtained graphene-copper composite thermally conductive film is tested to be 527.59 W / mK.

[0069] Example 7

[0070] (1) Roughening and patterning of copper foil: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling; the roughened copper foil is patterned by laser cutting to form small holes; the thickness of the copper foil is 30 μm, and the surface roughness is controlled by the thickness of the sandpaper and the rolling pressure; the rolling pressure is 10 MPa, and the mesh size of the sandpaper is 100 mesh; the aperture of the small holes is 2 mm, and the spacing is 5 mm;

[0071] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0072] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0073] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 5 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0074] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) is subjected to high-temperature treatment at 1000° C. under argon protection to repair the defective structure in the graphene film, and finally a graphene-copper composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

[0075] The ratio of the composite film thickness to the copper foil thickness in this embodiment is about 1:0.5, and the thermal conductivity of the obtained graphene-copper composite thermally conductive film is tested to be 529.41 W / mK.

[0076] Comparative Example 1

[0077] (1) Copper foil roughening treatment: The copper foil is placed between two pieces of sandpaper and a concave-convex structure is formed on its surface by rolling. The thickness of the copper foil is 20 μm, the rolling pressure is 10 MPa, and the mesh number of the sandpaper is 100 (no holes are punched);

[0078] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0079] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0080] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 8 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0081] (5) Preparation of composite thermally conductive film by high-temperature reduction: The composite film obtained in step (4) was subjected to a high-temperature treatment at 1000°C under argon protection. As a result, the obtained composite film showed a phenomenon that part of the graphene film was detached from the copper foil surface. This is because no through-patterning treatment was performed in Comparative Example 1, only a roughening treatment was performed, so the graphene film was not integrated with the metal film through the through holes, and the metal film was only tightly connected to the surface of the graphene film, and was not connected to each other through the small holes to form a whole. Compared with the process of patterning treatment in the present application, the graphene film of the product obtained in Comparative Example 1 is more likely to fall off from the copper foil surface, and there is a lack of metal films on the upper and lower surfaces of the graphene film to form a direct heat conduction channel, so the thermal conductivity will also be weaker.

[0082] Comparative Example 2

[0083] (1) Copper foil patterning: laser cutting is used to pattern the metal film to form small holes; the diameter of the small holes is 1 mm and the spacing is 3 mm; no roughening is performed;

[0084] (2) Cleaning and drying: The copper foil obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0085] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0086] (4) Preparation of composite film by reduction deposition: immersing the metal film in step (2) in a graphene oxide solution of target concentration, reacting at 40° C. for 8 h, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide;

[0087] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in step (4) was subjected to high-temperature treatment at 1000°C under argon protection. The composite film of Comparative Example 1 showed a phenomenon that part of the graphene film was detached from the copper foil surface. This was because no roughening treatment was performed in Comparative Example 2, but only patterned perforation treatment was performed. Although the metal film was able to form a whole with the graphene film through the small holes, the surface of the graphene film was not roughened. The connection strength between the metal film on the upper and lower surfaces of the graphene film and the graphene film was insufficient. Compared with the process of the present application in which both roughening treatment and patterned treatment were used, the graphene film of the product obtained in Comparative Example 2 was more likely to fall off from the copper foil surface, and the metal film on the upper and lower surfaces of the graphene film could not be in close contact with the graphene film, so the thermal conductivity would be weaker.

[0088] Comparative Example 3

[0089] (1) Cleaning and drying: The copper foil was sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature. The thickness of the copper foil was 20 μm. No roughening treatment or punching was performed.

[0090] (2) Cleaning and drying: The copper foil obtained in (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature;

[0091] (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a solid content of 1 wt%, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution;

[0092] (4) Preparation of composite film by reduction deposition: The metal film in (2) is immersed in a graphene oxide solution of target concentration, and the reaction time is 8 hours at 40°C. After the reaction is completed, the reduced graphene oxide film is taken out and dried, and then part of the reduced graphene oxide film is detached from the copper foil surface;

[0093] (5) Preparation of composite thermal conductive film by high-temperature reduction: The composite film obtained in (4) was subjected to high-temperature treatment at 1000°C under argon protection, and the graphene film was completely detached from the surface of the copper foil. This is because the copper foil in Comparative Example 3 was not roughened or patterned, and no adhesive was used. Therefore, the connection strength between the prepared graphene film and the metal film was very weak, so it was easier to fall off. In addition, the contact between the graphene film and the metal film was not close, so the thermal conductivity was also weaker.

[0094] Therefore, it can be known from the experimental results of the above embodiments and comparative examples that the technical solution of the present application, which performs both roughening and patterning treatment on the metal film, can not only increase the contact area between the graphene film and the underlying metal film through the roughening treatment, thereby improving the bonding strength between the metal and the graphene film; in addition, by patterning, regularly distributed small holes are formed on the metal film, so that the graphene films on the upper and lower surfaces of the metal film are connected to each other through the distributed small holes to form countless rivet points to form a whole and realize the tight coating of the graphene film on the metal layer, further reducing the possibility of the graphene film falling off from the metal film; and this is because the above-mentioned roughening treatment and patterning treatment make the metal film and the graphene film form a whole, so the metal and the graphene film can be in close contact, and no adhesive is needed, and the thermal conductivity of the obtained metal-graphene composite thermal conductive film can be improved without the use of an adhesive.

Claims

1. A method for preparing a coated metal-graphene composite thermally conductive film, characterized in that: The steps of the method include: (1) Roughening and patterning of metal film: The metal film is placed between two pieces of sandpaper and a concave-convex structure is formed on the surface of the metal film by rolling. Then, the roughened metal film is patterned by laser cutting to form small holes. (2) Cleaning and drying: The metal film obtained in step (1) is sequentially immersed in a dilute hydrochloric acid solution, deionized water, and ethanol for ultrasonic cleaning to remove the oxide layer and impurities on the metal surface, and then dried at room temperature; (3) Preparation of graphene oxide slurry: preparing a graphene oxide solution with a desired solid content concentration, and performing high-pressure homogenization treatment to obtain a well-exfoliated graphene oxide solution; (4) preparing a composite film by reduction deposition: immersing the metal film in step (2) in the graphene oxide solution of the target concentration obtained in step (3), adjusting the reaction temperature and reaction time to control the deposition thickness of the coated graphene film, and after the reaction is completed, taking out and drying to obtain a metal film initially coated with reduced graphene oxide, i.e., a composite film; (5) Preparation of composite thermal conductive film by high temperature reduction: The composite film obtained in step (4) is subjected to high temperature treatment at 950-1100° C. to repair the defective structure in the graphene film, and finally a graphene-metal composite thermal conductive film with excellent thermal conductivity is obtained by calendering.

2. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The metal film described in step (1) is selected from one of copper foil, aluminum foil and silver foil.

3. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 2, characterized in that: The metal film described in step (1) is copper foil.

4. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The thickness of the metal film in step (1) is 20-50 μm.

5. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The rolling pressure described in step (1) is selected to be 10-30 MPa.

6. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The aperture of the small holes described in step (1) is 0.5-2 mm, and the spacing is 1-5 mm.

7. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The required concentration described in step (3) is a solid content concentration of the graphene oxide solution ≥ 1wt%.

8. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The overall thickness of the composite film obtained in step (4) does not exceed 100 um, and the ratio of the thickness of the composite film to the thickness of the metal film is set in the range of 1:0.25-1.

9. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The reaction temperature and reaction time in step (4) are 35-45° C. for 5-8 hours.

10. The method for preparing the coated metal-graphene composite thermally conductive film according to claim 1, characterized in that: The composite membrane obtained in step (5) is subjected to a high temperature treatment at 1000°C.